2018
DOI: 10.1111/ped.13548
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and overall health in high school children: Results from the Toyama birth cohort study, Japan

Abstract: Undesirable lifestyle was associated with poor health status in high school boys and girls. Further understanding of these relationships is needed to facilitate the development of interventions that will help children with poor health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Similarly, they found that girls who skipped breakfast, and had night-time eating patterns, personal computer use >4 h per day, and short night-time sleep duration, ≤6 h/night, were more likely to exhibit poor health status. Poorer health status predicted lower academic performance in both sexes (sex-independent finding) [21]. Likewise, in our study we did see that there is a significant relationship between students success and their status as per meal-skipping, with students skipping meals performing lower in terms of TEOG scores.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, they found that girls who skipped breakfast, and had night-time eating patterns, personal computer use >4 h per day, and short night-time sleep duration, ≤6 h/night, were more likely to exhibit poor health status. Poorer health status predicted lower academic performance in both sexes (sex-independent finding) [21]. Likewise, in our study we did see that there is a significant relationship between students success and their status as per meal-skipping, with students skipping meals performing lower in terms of TEOG scores.…”
Section: Discussionsupporting
confidence: 77%
“…Nine studies did not find a significant association [ 35 , 40 , 48 , 51 , 63 , 65 , 81 , 89 , 90 ]. Two studies observed a significant relationship between SB and SRH for girls only [ 3 , 39 ], and one study found a significant relationship for boys only [ 44 ] (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the effect size value using an odds ratio for a binary categorical outcome, prior research suggests that a log odds greater than 2.0 or less than 0.5 is considered a large effect size [ 98 ]. A number of studies reported an odds ratio above 2.0 or below 0.5 [ 1 , 3 , 4 , 39 , 43 , 46 , 54 , 60 , 68 , 79 , 82 ], suggesting a large effect size.…”
Section: Discussionmentioning
confidence: 99%
“…Child lifestyles were assessed based on breakfast consumption, nighttime sleep duration, screen time in h/ day, and after-school "cram school" attendance. Here, "breakfast consumption" [10,27] was classified into two categories, "eat every day" and "skipping breakfast," while "nighttime sleep duration" [23] was categorized according to the number of sleeping hours (i.e., "more than 8 hours" and "less than 8 hours"). This was based on previous research indicating that Japanese elementary schoolchildren average approximately 8.5 h of sleep per night [25].…”
Section: Child Lifestyle Factorsmentioning
confidence: 99%